GEOLOGY AND STRUCTURAL EVOLUTION OF THE MURUNTAU GOLD DEPOSIT, KYZYLKUM DESERT, UZBEKISTAN - Drew L.J.; Berger B.R.; Kurbanov N.K. (My University, 1996)
The Muruntau gold deposit in the Kyzylkum desert of Uzbekistan is the largest single deposit (> 1100 tonnes of gold) of the class of low-sulfide syndeformation/synigenous gold deposits formed in the brittle/ductile transition zone of the crust within transpressional shear zones. Hosted by the Cambrian to Ordovician Besopan Suite, the ores were deposited in pre-existing thrust-fault- and metamorphism-related permeabilities and in synmineralization dilational zones created in a large fault-related fold. The Besopan Suite is a 5,000-m-thick sequence of turbiditic siltstones, shales and sandstones. The ore is primarily localized at the base of the Besopan-3 unit, which is a 2,000-m-thick series of carbonaceous shales, siltstones, sandstones and cherts. Initial gold deposition took place within the Sangruntau-Tamdytau shear zone, which was developed along the stratigraphic contact between the Besopan-3 and Besopan-4 units. During the mineralization process, folding of the Besopan Suite and a left-step adjustment in the Sangruntau-Tamdytau shear zone were caused by two concurrent events: (1) the activation of the left-lateral Muruntau-Daugyztau shear zone that developed at nearly a 90° angle to the preceding shear zone and (2) the intrusion of granitoid plutons. These structural events also resulted in the refocusing of hydrothermal fluid flow into new zones of permeability.
Keywords: Ordovician; Cambrian; Палеозой::Ордовикская; Paleozoic::Cambrian; Paleozoic::Ordovician; Палеозой::Кембрийская